The Efficacy and Safety of Abaloparatide‐SC in Men With Osteoporosis: A Randomized Clinical Trial. (18th October 2022) - Czerwinski, Edward; Cardona, Jose; Plebanski, Rafal; Recknor, Chris; Vokes, Tamara; Saag, Kenneth G; Binkley, Neil; Lewiecki, E Michael; Adachi, Jonathan; Knychas, Dorota; Kendler, David; Orwoll, Eric; et al.
ABSTRACT: Abaloparatide significantly increased bone mineral density (BMD) in women with postmenopausal osteoporosis and decreased risk of vertebral, nonvertebral, and clinical fractures compared with placebo. The Abaloparatide for the Treatment of Men with Osteoporosis (ATOM; NCT03512262) study evaluated the efficacy and safety of abaloparatide compared with placebo in men. Eligible men aged 40 to 85 years with osteoporosis were randomized 2:1 to daily subcutaneous injections of abaloparatide 80 μg or placebo for 12 months. The primary endpoint was change from baseline in lumbar spine BMD. Key secondary endpoints included BMD change from baseline at the total hip and femoral neck. A total of 228 men were randomized (abaloparatide, n  = 149; placebo, n  = 79). Baseline characteristics were similar across treatment groups (mean age, 68.3 years; mean lumbar spine BMD T ‐score, −2.1). At 12 months, BMD gains were greater with abaloparatide compared with placebo at the lumbar spine (least squares mean percentage change [standard error]: 8.48 [0.54] versus 1.17 [0.72]), total hip (2.14 [0.27] versus 0.01 [0.35]), and femoral neck (2.98 [0.34] versus 0.15 [0.45]) (all p  < 0.0001). The most common (≥5%) treatment‐emergent adverse events were injection site reaction, dizziness, nasopharyngitis, arthralgia, bronchitis, hypertension, and headache. During 12 months of abaloparatide treatment, men with osteoporosis exhibited rapid and significant improvements in BMD with a safety profile consistent with previous studies. These results suggest abaloparatide can be considered as an effective anabolic treatment option for men with osteoporosis. © 2022 Radius Health Inc and The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR). Abstract : Change from baseline in bone mineral density. * p  < 0.0001. In men with osteoporosis, least squares mean percentage change (standard error) from baseline in lumbar spine BMD at 12 months was 8.48% (0.54%) with abaloparatide compared with 1.17% (0.72%) with placebo ( p  < 0.0001).